Factores de riesgo asociados al embarazo en adolescentes en el Centro de Salud Universitario Motupe de Loja - Martínez Reátegui, Samantha Lizbeth (2023)
Adolescent pregnancy is considered a public health problem of great magnitude as an effect of exposure to different components of the environment during the development period. In adolescence, physical, cognitive and psychosocial changes are acquired, creating a behavioral pattern that can protect or put health at risk. Therefore, the present degree work was proposed whose objective was to determine the risk factors associated with pregnancy in adolescents at the Motupe University Health Center in Loja. This was a cross-sectional case-control study with a quantitative approach in which 10 pregnant adolescents (cases) and 20 non-pregnant adolescents (controls) between 10 and 19 years of age participated. The "Data collection form for cases and controls" was used to obtain the information; the point prevalence formula and the Odds Ratio (OR) measure of association were used for the statistical analysis. The results found in relation to the demographic characteristics, 100% are pregnant adolescents between 15 and 19 years of age, mostly with secondary education. Regarding the prevalence in the period JanuaryJune 2022, 7 out of every 100 young women are pregnant. On the other hand, personal, family and socioeconomic aspects were not identified as risk factors for adolescent pregnancy; however, the indicator of education on contraceptive methods was found to be a protective factor (OR= 0.11). In conclusion, no risk factors were identified in the present study, and there is a low prevalence of cases associated with adolescent pregnancy